AZITROMYCIN EFFICACY IN TREATMENT OF PEDIATRIC OUT-OF-HOSPITAL INFECTIONS - L. V. Kozlova (Вопросы современной педиатрии, 2012)
Macrolides remain one of the most popular types of antibiotics prescribed in the outpatient’s clinic and also are second most popular after penicillins in the amount of consumption. Activity against the majority of respiratory pathogens, including atypical ones, high tolerability, presence of special nonantimicrobal features that are unique for medications of this class — all this make them a favourable choice for bacterial out-of-hospital infections treatment. This article contains comparative analysis of drugs of this class. The role of azithromycin in pediatric respiratory out-of-hospital infections treatment is discussed.